Harvesting methods of Cinnamomum tamala leaves in private land: a case study from Udayapur district, Nepal - Lamichhane, D; Karna, NK (Banko Janakari, 2010)
Tejpat (Cinnamomum tamala) leaf is commercially one of the important non-timber forest products of Nepal. This paper attempts to elaborate and analyze the harvesting methods and techniques of Tejpat grown by the farmers in their private land. The study was conducted in the villages of Udayapur district where Tejpat was widely cultivated and harvested for income generation and trading purposes. Almost all farmers with private land had planted Tejpat. Complete lopping of leaves once a year was the exclusive practice for harvesting. The collection period for leaf was from Ashoj (October) to Magh (February) but the period for bark varied greatly, i.e. from Kartik to Poush (November to January) and Baisakh / Jestha (May / June). Bark collection was done only from old, dying, diseased and low leaf producing trees. Average number of trees per household ranged from 10 to 155. The mean diameter at breast height (DBH) of the trees was 39.58 cm. There was high positive correlation between the DBH and fresh weight of leaf. Fitting of linear regression of fresh weight of leaf with DBH proved that the relationship was statistically significant at 5% level of significance. The minimum age and size of trees for leaf harvesting were found to be five years and 16.18 cm, respectively. Keywords: Fresh weight; harvesting; private land; Tejpat DOI: 10.3126/banko.v19i2.2981 Banko Janakari, Vol. 19, No.2 2009 pp.20-24